Life assessment of power transformer via furans analysis [electronic resource] - 176531 Zalizah Poniran (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2006